-2(x+4)=x-8+3(2x+1)

Simple and best practice solution for -2(x+4)=x-8+3(2x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(x+4)=x-8+3(2x+1) equation:



-2(x+4)=x-8+3(2x+1)
We move all terms to the left:
-2(x+4)-(x-8+3(2x+1))=0
We multiply parentheses
-2x-(x-8+3(2x+1))-8=0
We calculate terms in parentheses: -(x-8+3(2x+1)), so:
x-8+3(2x+1)
determiningTheFunctionDomain x+3(2x+1)-8
We multiply parentheses
x+6x+3-8
We add all the numbers together, and all the variables
7x-5
Back to the equation:
-(7x-5)
We get rid of parentheses
-2x-7x+5-8=0
We add all the numbers together, and all the variables
-9x-3=0
We move all terms containing x to the left, all other terms to the right
-9x=3
x=3/-9
x=-1/3

See similar equations:

| -1+2x=-x+9 | | X-4x-7=-2x+5 | | 25x-80=13x+160 | | 1/2x+2/3=3/2/3 | | -16p-5(4-5p)=5(p-4)-32 | | 5/2(3x-2)=4/5(x-4) | | 8x+4+10x-8=180 | | f(9)=20 | | -24=-14-5x | | 7t-3+4t=-26 | | r+25=7 | | 6.7-3.1x=10.66 | | x-10=9-3x | | 22+6n=14+12n | | 6x+6-x=42 | | -16p`5(4-5p)=5(p-4)-32 | | 4r+35=18 | | X*2-3-x+4=x+2 | | 3x-1+x=3x+2 | | 2(x-1)=14,x= | | -17w-8=-10 | | 68=3y+8 | | 3+7|n/6|=10 | | 14+.25x=2x | | 4x+16=2x-12 | | -2(-9y+8)-3y=5(y-5)-5 | | 150x+2=195-1x | | -14x=20 | | |x/3|-7=-6 | | -1x+5=0 | | 10t-2=12t-10 | | 2x+8=6(6+5x) |

Equations solver categories